2019
DOI: 10.1093/ecco-jcc/jjz013
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Infections in Inflammatory Bowel Disease, and Their Relationship With Immunosuppressive Therapy and Their Effects on Disease Mortality

Abstract: Background and Aims There is controversy as to whether the risk of relevant infection in IBD is related to immunosuppressants or the disease itself. The aims of this study were to evaluate: [1] the life-long prevalence and types of relevant infections in patients with IBD related to immunosuppressive treatment, and [2] the relationship of both infection and patient comorbidity to mortality. Methods Observational multicentre r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
4
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 53 publications
2
54
4
6
Order By: Relevance
“…Thus, the case numbers are too low to allow reliable conclusions to be drawn. Without doubt, the overall risk of bacterial and viral infections is significantly increased in patients under immunosuppressive therapy or steroids; these drugs also cause increased mortality [39]. Epidemiological studies from Lombardy in Italy including 1,193 patients with psoriasis receiving biologics show an increased risk for infection, but not for severe disease, as defined by a need for intensive medical care, or death (see ▶ Table 3) [40].…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the case numbers are too low to allow reliable conclusions to be drawn. Without doubt, the overall risk of bacterial and viral infections is significantly increased in patients under immunosuppressive therapy or steroids; these drugs also cause increased mortality [39]. Epidemiological studies from Lombardy in Italy including 1,193 patients with psoriasis receiving biologics show an increased risk for infection, but not for severe disease, as defined by a need for intensive medical care, or death (see ▶ Table 3) [40].…”
Section: Recommendationmentioning
confidence: 99%
“…patients with low risk face mask (covering the mouth and nose) gloves protective goggles or protective visor waterproof long-sleeved single-use gown patients with high risk positive COVID-19 diagnosis FFP2 or FFP3 mask double gloves hair protection protective goggles or protective visor waterproof long-sleeved single-use gown Without any doubt, the overall risk of bacterial and viral infections is significantly increased in patients under immunosuppressive or steroid therapy; these drugs also cause increased mortality [39]. In contrast, treatment with vedolizumab does not seem to increase the risk of respiratory tract infection [52].…”
Section: Drug Therapiesmentioning
confidence: 99%
“…Ohne Zweifel ist insgesamt das Risiko für Infektionen bei Patienten mit einer immunsuppressiven Therapie bzw. einer Steroidmedikation signifikant erhöht; diese bedingen auch eine erhöhte Mortalität [39]. Im Gegensatz dazu scheint die Behandlung z.…”
Section: Medikamentöse Therapieunclassified
“…Since then, great concern has been raised regarding the impact of this disease on specific populations at a higher risk for infection, such as IBD patients. Several previous reports have well described the association among immunosuppressive treatment, disease activity, and malnutrition, with a higher frequency and severity of infections in IBD patients [3, 4]. However, it is still uncertain whether these features constitute additional risks for SARS-CoV-2 infection beyond those already described for the general population, such as elderly, pregnant, hypertensive, and diabetic patients [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with inflammatory bowel disease (IBD), especially those on immunosuppressive therapies or with active disease, the current pandemic requires several new considerations. Previous studies have shown that disease activity and exposure to thiopurines increase the risk of viral infections [3, 4]. However, there is expert agreement that IBD patients are not at a greater risk of developing SARS-CoV-2 infection than the general population [5].…”
Section: Introductionmentioning
confidence: 99%